Topographic change quantification and DEM uncertainty assessment using TanDEM-X and F-SAR DEM time series and quality maps: Application to the 2014-2015 Bárðarbunga volcanic eruption, Iceland - Dirscherl, Mariel Christina (2016)
Topographical information is of fundamental interest for a wide range of disciplines including glaciology, agriculture, communication network planning, or hazard management. In volcanology, elevation data is of particular interest when assessing material flows throughout a volcanic system. To obtain accurate estimates of time-varying topography in volcanic active regions, high-resolution digital elevation models (DEMs) are required. Whilst ground-based GPS measurements and photogrammetry are restricted in terms of temporal and spatial resolution, the monitoring with airborne laser scanning (LiDAR) depends upon meteorological and illumination conditions and is limited by volcanic ash clouds. The use of space- and airborne synthetic aperture radar (SAR) overcomes such issues and allows the generation of medium- to high-resolution DEMs with interferometric techniques (InSAR). To monitor and evaluate topographical changes and especially volumetric gains and losses during the 2014-2015 Bárðarbunga eruption, Iceland, time sequences of TanDEM-X and F-SAR InSAR DEMs were evaluated differencing pairs of elevation models. The 2014-2015 volcanic eruption was associated with the rare event of a caldera collapse, visible on the surface of the Vatnajökull glacier, as well as a major effusive eruption in the Holuhraun plain. In order to guarantee the reliability of the topographical analysis at both locations, DEM absolute and relative height errors were investigated and raised the importance of accounting for the impact of system parameters, the SAR processing and the local environment before processing the DEMs. Acquisitions over the snow-covered Bárðarbunga caldera were especially affected by microwave penetration into snow and DEMs over the Holuhraun lava field implied large height errors due to fast moving lava flows. Considering the TanDEM-X dataset, the topographical analysis over the Bárðarbunga caldera revealed a total volume loss of approximately -1.40 ± 0.13 km3 and the volume gain of the generated lava field was ...